Balance ability and all-cause death in middle-aged and older adults: A prospective cohort study - Xie, Kaihong; Han, Xiao; Hu, Xuanhan (Frontiers in Public Health, 2023)
Objective To explore the relationship between balance ability and all-cause death in middle-aged and elderly people, and to provide a basis for formulating a balanced training plan for middle-aged and elderly people in China. Methods We selected 1,8888 participants from the China Health and Retirement Study (CHARLS) in 2011, 2013, 2015, and 2018. Cox proportional hazard models were constructed to evaluate the effect of balance ability on death events. Interactions were explored about chronic disease, overweight and obesity. Results We found an association between balance ability and death among middle-aged and elderly people. Multivariate Cox proportional hazard regression model analysis showed that the risk of death decreased 10% for every second increase in the balance ability (HR=0.90,95%CI:0.85-0.95). With balance ability ＜10 s as the reference group, the adjusted HRs were 0.60 (0.44-0.83) among the participants. The death density of balance ability ＜10 s was 73.87 per thousand person-years higher than that balance ability≥10 s. There was no interaction between balance ability and chronic disease, as well as overweight and obesity (P＞0.05). Conclusion Balance ability below 10 s is inversely associated with death risk among middle-aged and elderly people. This relationship may not be related to chronic disease, as well as overweight and obesity.